Dementia Prevalence, Comorbidities, and Lifestyle Among Jatinangor Elders - Ong, Paulus Anam; Annisafitrie, Febby Rosa; Purnamasari, Novita; Calista, Chandra; Sagita, Noveline; Sofiatin, Yulia; Dikot, Yustiani (Frontiers in Neurology, 2021)
Abstract Introduction: Research on dementia prevalence, and the potentially related risk factors from Indonesia are scarce. We sought to identify the prevalence of dementia, health risk factors, and lifestyle in Jatinangor elders. Methods: A total of 686 participants completed questionnaires on lifestyle, health risk factors, cognitive and functional tests from September 2013 to December 2013. The prevalence of dementia was determined, and the associations between health, leisure activities, dietary pattern, and dementia were analysed using logistic regression. Results: The prevalence of dementia was 29.15%. The risk factors differed between age groups. Those aged 60-74 years, a lower education level, lower occupational attainment, and less active intellectual and recreational activities were associated with higher dementia risk. Those aged >75 years, living in a rural area and taking less fruit associated with a higher risk of dementia. Conclusions: The prevalence of dementia in Jatinangor is high. The identified modifiable risk factors are a potential target for intervention and useful for designing public health policies